THE NEED FOR DEVELOPMENT OF TOURISM COMPONENTS IN LINGSAR TEMPLE WEST LOMBOK DISTRICT - Ni Putu Rika Sukmadewi; Komang Sriyasa (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2019)
Lingsar Temple is a historical heritage and is a cultural preserve that is still maintained. Lingsar Temple has several very unique cultural potentials, such as the heritage of historical buildings such as temples, spring pools used for melukat and cultural acculturation. This study aims to determine the components of tourism in the development of Lingsar Temple as an effort to increase tourist visits. The method used in this study is a qualitative research method. The development of tourism in an area is strongly influenced by the level of supply of tourism components, namely something to see, something to buy, and something to do. In this study it can be concluded that Lingsar Temple has fulfilled the three tourism components, namely something to see, something to do and something to buy, but further management and cooperation between the local government and local communities is needed to manage Lingsar Temple as an effort to attract tourist visits. Keywords: Development, Tourism Components, Lingsar Temple